EVALUATION OF THE IMPLEMENTATION OF THE PREPARATION OF MICRO BUSINESS FINANCIAL REPORTS BASED ON SAK EMKM CASE STUDY ON BALABO SCRAP - Ravika Permata Hati; Aprilia Merisca; Rizki Eka Putra; Aznedra Aznedra (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to determine whether accounting records for MSMEs in the Balabo Scrap are in accordance with the Micro, Small, and Medium Entity Financial Accounting Standards (SAK EMKM). The data analysis method used is descriptive qualitative analysis method which is a description of the result of interview and conducting comparisons of financial statements on MSMEs that are appropriate and not in accordance with the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM). The object in this study is the accounting records section on Balabo Scrap. The results of this study indicate that the Accounting Records in The Balabo Scrap are not yet in accordance with the Micro, Small, and Medium Entity Financial Accounting Standards (SAK EMKM) due to a lack of knowledge about accounting records and lack of socialization about SAK EMKM.